Vandkunsten. Danish Co-housing - Ferrer Forés, Jaime J. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Confronted with the large mass housing developments on the urban peripheries, the Danish collective Vandkunsten conceived, in the late sixties, pioneering low-rise, high-density cooperative residential communities in Tinggården, Herfølge (1971-1978), Hedelyngen in Herlev (1981), Trudeslund in Birkerød (1979-1981), Fuglsangpark, Farum (1981-1983), Hesselbo, Værløse (1983-1984) and Jystrup Savværk (1983-1984) that promote the participation of residents in the design process and community life. These experimental groupings shape collective life in a way that transcends the mere grouping or stacking of houses, combining privacy, sociability, flexibility, environmental commitment and energy self-sufficiency. Vandkunsten's projects are a social construct that promotes a community in an architecture with soft edges and industrial and vernacular textures that welcome a shared and cooperative life.
Keywords: Community; Housing; Co-housing; Bofællesskab; Vandkunsten; Denmark